PERAN KETERAMPILAN KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Abdul Rohim; Dewi Irayanti (STIE PGRI Dewantara Jombang, 2022)
The purpose of this study was to explain the effect of the variable Work Skills and Work Experience on Work Productivity of Employees Assembling Infusion of PT. Jayamas Medica Industri Jombang. This study uses a quantitative approach with explanatory research methods which are carried out through data collection in the field. The population used is the Assembling Employees of the Infusion Section of PT. Jayamas Medica Industri Jombang, totaling 45 employees. The sampling technique used was the saturated sample technique. The data analysis method uses validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test through T test and coefficient of determination (R2) with the help of SPSS Version 21. Based on the results of the study, it showed that Job Skills was able to increase Work Productivity of Assembling Employees in the infusion section of PT. Jayamas Medica Industri Jombang. Work Experience is able to increase Work Productivity of Assembling Employees in the infusion section of PT.Jayamas Medica Industri Jombang.